Importance of Areas of Preparation for Teaching in Rural/Small Schools - Jerry G. Horn; Patricia Davis; Robert Hilt (Journal of Research in Rural Education, 1985)
Throughout the literature, reference is made to the unique qualifications for teaching in rural/small schools. At the same time, colleges and universities are criticized for reluctance in designing teacher education programs in rural education. This study investigated the importance of forty-five (45) selected areas of preparation for teaching success in small schools of Kansas. The 162 respondents (subjects) were recent college graduates who were teaching in schools of 600 or fewer students. The areas of preparation, normally addressed in a general teacher education program, were categorized as General Studies/Teaching Specialty, Studies in Foundations of Education, Studies in Curriculum and Instruction, and Studies in Selected Professional Skills. Based on analysis of the respondents' rating of each of the 45 items on a 1-5 scale, all but two areas were judged to be above the mid-point of the scale in importance. As a group, the areas of Oral Communications, Controlling Discipline, Organizing and Managing the Classroom, Teaching Major Specialty and Motivating Students were rated highest. Little difference was observed between the perceptions of teachers in very small schools and larger schools, 1-300 and 301-600 students, respectively